Minimizing THD Using a Multilevel Inverter Integrated with MPPT - Andi Syarifuddin; Pakka, Hariani Ma’tang; Halit Eren; Ahmed Saeed AlGhamdi; Umar, Umar; Widya Wisanti; Amelya Indah Pratiwi (JURNAL NASIONAL TEKNIK ELEKTRO, 2025)
This paper presents a novel Modified Multilevel Inverter (MMLI) topology to reduce Total Harmonic Distortion (THD) in photovoltaic (PV) systems. Unlike conventional Cascaded H-Bridge Inverters, the proposed MMLI achieves higher output voltage levels using fewer switching components by optimizing the arrangement of voltage sources and switches. A Boost converter integrated with Maximum Power Point Tracking (MPPT) further enhances power conversion efficiency and system stability. This specific configuration has not been previously explored, offering a more effective solution for THD mitigation. Simulations conducted in MATLAB/Simulink demonstrate the inverter’s performance, with the 5-level MMLI achieving a THD of 28.99% and the 9-level configuration reducing it to 18.15%. These results confirm the superiority of the proposed topology in improving power quality and reducing system complexity. Moreover, the design eliminates the need for external filters, making it a cost-effective and practical option for grid-connected PV applications.